Fiber optic Fabry-Perot interferometer sensor: an efficient and fast approach for ammonia gas sensing - Kanawade, Rajesh; Kumar, Ajay; Pawar, Dnyandeo; Late, Dattatray; Mondal, Samir; Sinha, Ravindra K. (Journal of the Optical Society of America B-Optical Physics, 2019)
In this work, we propose and demonstrate a Fabry-Perot-interferometer-based polydimethylsiloxane (PDMS) and poly(methyl methacrylate) (PMMA)-composite-coated optical sensor for ammonia and volatile organic compounds (VOCs) detection at room temperature. The principle of sensing is based on change in the cavity length of the FP cavity in the presence of varied concentrations of gases, which results in changes in the total reflectance due to the shift in wavelength of an interference pattern. The sensing composite material was coated on a single-mode optical fiber by using a simple dip-coating technique and explored it for sensing. The ammonia and VOCs measurements were performed for concentrations ranging from 5 to 500 ppm. The corresponding sensitivity and limit of detection of the developed sensor for ammonia gas detection was observed of the order of around 4.16 pm/ppm and 4.8 ppm, respectively. The response and recovery times of the sensor were found to be of the order of 50 s and 10 s, respectively, for the ammonia gas. This sensor provides a simple, cost-effective, highly sensitive, and repeatable approach to measure ammonia gas and other VOCs at room temperature and could fulfill the demands of industrial applications. (C) 2019 Optical Society of America

Negative axicon tip-based fiber optic interferometer cavity sensor for volatile gas sensing - Kanavvade, Rajesh; Kumar, Ajay; Pawar, Dnyandeo; Vairagi, Kaushal; Late, Dattatray; Sarkar, Sudipta; Sinha, Ravindra K.; Mondal, Samir (Optics Express, 2019)
In this research work we demonstrated negative axicon optical fiber tip filled with Polydimethylsiloxane (PDMS) as a sensor platform for volatile organic gases detection at room temperature. The response of the sensor was measured with various Volatile Organic Compounds (VOCs) such as Chloroform, Hexane, Isopropanol, Acetone, Toluene and Methanol in the concentration ranging from 5 to 200 ppm. The corresponding sensitivity and limit of detection (LOD) of the developed sensor for the measured VOCs were observed between the order of around 23.7 to 3.2 pm/ppm and 0.84 to 6.10 ppm, respectively. The response and recovery time of sensor were found between the order of 30 to 57 seconds and 8 to 25 seconds respectively for the measured VOCs. Thermal stability of the developed sensor was also studied at 30-70 degrees C with intervals of 10 degrees C. The principle of sensing is based on change in the length of the Fabry-Perot Interferometric (FPI) cavity in the presence of varied concentrations of VOCs, which results in changes in the shift in wavelength of an interference pattern attributed to the change in PDMS filling the cavity length (swelling). The experimentally observed trends in the relative swelling of PDMS with VOCs are found in agreement with the theoretically calculated values obtained from the Hansen solubility parameter (HSP). The developed gas sensor has the potential to fulfill the demands of industrial applications.

Skin mimicking solid optical tissue phantom fulfillment and its characterization - Kumar, Ajay; Hinge, Sarika; Dixit, Hemant; Kanawade, Rajesh; Kulkarni, Gauri (Photonics in Dermatology and Plastic Surgery 2022, 2022)
Skin mimicking optical tissue phantoms are widely used in diagnostics systems for characterization, optimization, routine calibration and validation. In general, solid phantoms are more preferred in comparison to liquid phantoms. Therefore, our aim is to prepare and characterize the solid tissue phantoms having skin equivalent optical properties. In this work, we have used epoxy resin and hardener as a base material and titanium oxide (TiO2) nanoparticles and ink as a scatterer and absorber media, respectively. The total transmission (Tt), collimated transmission (Tc), and diffuse reflectance (Rd) spectra of the developed phantoms were measured with an integrating sphere installed in UV-VIS spectrometer within the wavelength range 400-700 nm. To characterize the optical properties such as absorption (mu(a)), reduced scattering (mu(s)'), and anisotropy factor (g) of the developed tissue phantoms, the numerical model based on Inverse Adding Doubling (IAD) has been used. With various concentrations of absorber and scatterer, a calibration curve was prepared. The calculated experimental optical properties from IAD matched with the predicted intrinsic optical properties of the skin. Thus, the preliminary results suggest that the recipe used in this study may be used as an alternative approach to developing skin mimicking solid optical phantom for diagnostics system applications.
Keywords: Absorption; anisotropy factor; scattering; skin mimicking; solid tissue phantom

Response of cardiac pulse parameters in humans at various inclinations via 360° rotating platform for simulated microgravity perspective - Jagtap, Sagar; Kumar, Ajay; Mahale, Bhoopesh; Dixit, Jyotsana; Kalange, Ashok E.; Kanawade, Rajesh; Gangal, Shashikala; Vidyasagar, Pandit (NPJ Microgravity, 2023)
On the Earth, the human body is designed and adapted to function under uniform gravitational acceleration. However, exposure to microgravity or weightlessness as experienced by astronauts in space causes significant alterations in the functioning of the human cardiovascular system. Due to limitations in using real microgravity platforms, researchers opted for various ground-based microgravity analogs including head-down tilt (HDT) at fixed inclination. However, in the present study, an investigation of response of various cardiac parameters and their circulatory adaptation in 18 healthy male subjects was undertaken by using an indigenously developed 360 & DEG; rotating platform. Cardiac pulse was recorded from 0 & DEG; to 360 & DEG; in steps of 30 & DEG; inclination using piezoelectric pulse sensor (MLT1010) and associated cardiac parameters were analyzed. The results showed significant changes in the pulse shape while an interesting oscillating pattern was observed in associated cardiac parameters when rotated from 0 & DEG; to 360 & DEG;. The response of cardiac parameters became normal after returning to supine posture indicating the ability of the cardiovascular system to reversibly adapt to the postural changes. The observed changes in cardiac parameters at an inclination of 270 & DEG;, in particular, were found to be comparable with spaceflight studies. Based on the obtained results and the proposed extended version of fluid redistribution mechanism, we herewith hypothesize that the rotation of a subject to head down tilt inclination (270 & DEG;) along with other inclinations could represent a better microgravity analog for understanding the cumulative cardiac response of astronauts in space, particularly for short duration space missions.

Synthesis, biological evaluation and docking studies of silicon incorporated diarylpyrroles as MmpL3 inhibitors: an effective strategy towards development of potent anti-tubercular agents - Vasudevan, N.; Motiwala, Zenia; Ramesh, Remya; Wagh, Sachin B.; Shingare, Rahul D.; Katte, Revansiddha; Anand, Amitesh; Choudhary, Sushil; Kumar, Ajay; Gokhale, Rajesh S.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2023)
Growing global demand for new molecules to treat tuberculosis has created an urgent need to develop novel strategies to combat the menace. BM212 related compounds were found to be potent anti-TB agents and they inhibit mycolic acid transporter, MmpL3, a known potent drug target from Mycobacterium tuberculosis. In order to enhance their inhibitory potency, several silicon analogues of diarylpyrroles related to BM212 were designed, synthesized, and evaluated for anti-tubercular activities. In Alamar blue assay, most of the silicon-incorporated compounds were found to be more potent than the parent compound (BM212), against Mycobacterium tuberculosis (MIC = 1.7 & mu;M, H37Rv). Docking results from the crystal structure of MmpL3 and silicon analogues as pharmacophore model also strongly correlate with the biological assays and suggest that the incorporation of silicon in the inhibitor scaffold could enhance their potency by stabilizing the hydrophobic residues at the binding pocket. The best docking hit, compound 12 showed an MIC of 0.1 & mu;M against H37Rv with an acceptable in vitro ADME profile and excellent selectivity index. Overall, the present study indicates that, the designed silicon analogues, especially compound 12 could be a good inhibitor for an intrinsically flexible drug-binding pocket of MmpL3 and has potential for further development as anti-tubercular agents.
Keywords: antibiotic; BM212; docking studies; MmpL3 inhibitor; Silicon analogue; tuberculosis

Fabrication and evaluation of a spatially resolved fiber-optic probe for diffuse reflectance measurement for noninvasive diabetic foot ulcer diagnosis perspective - Kumar, Ajay; Hattale, Gangadhar; Pawar, Dnyandeo; Kanawade, Rajesh (Optical Engineering, 2024)
Timely diagnosis and monitoring of wound progression or healing are key to improving the long-term outcome of diabetic foot ulcers (DFU). Diffuse reflectance spectroscopy (DRS) has the potential to noninvasively diagnose the DFU in real time, as it detects changes in local blood volume fraction and oxygenation state level that occur when tissue becomes diseased or ulcerated. Since foot soles have a thicker epidermis and deeper blood vessels/capillaries than other parts of the body, a spatially resolved fiber-optic probe (SRFP) is needed to detect the optimal spatially resolved diffuse reflectance (SRDR) signal from the local site of the ulcer for DFU diagnosis. Therefore, herein, an SRFP consisting of a linear array of seven 400-mu m fibers with detector-source (D-S) fiber separation (rho) ranging from 0.8 to 4.8 mm was designed, fabricated, tested, and evaluated for SRDR measurement from a standard reflectance plate of barium sulfate (BaSO4) and foot sole of 27 healthy human subjects. The variation in SRDR spectra for each detector and source fiber pair measured with BaSO4 was found to be less than 1.6%. In-vivo measurements from the foot sole demonstrate that the fabricated probe has the ability to spatially resolve and distinguish the SRDR spectra from sites, namely, the fifth metatarsal, ball of great joint, calcaneum, and great toe. Experimentally and theoretically, the detector and source fiber pair of rho=1.6 and 2.4 mm were optimal for SRDR measurements from a human foot. To evaluate and validate the performance of SRFP in a context relevant to DFU diagnosis, further SRDS measurements were performed on the solid tissue phantoms that mimic the optical properties of the normal and diabetic foot sole, and their results are statistically found different. Preliminary results suggest that developed SRFP can be explored for DRS measurement from foot ulcer patients to confirm its potential clinical applicability.
Keywords: diabetic foot ulcer; diffuse reflectance spectroscopy; foot sole; spatially resolved fiber-optic probe; tissue phantom

Normal and diabetic foot sole skin mimicking tissue phantom fulfillment for spectroscopic-based DFU diagnostics perspective - Kumar, Ajay; Hattale, Gangadhar; Hinge, Sarika; Kulkarni, Gauri; Late, Dattatray J.; Kanawade, Rajesh (AIP ADVANCES, 2024)
Keywords: OPTICAL-PROPERTIES; STATE

Polymeric PEI/PEG coated optical fiber fabry-perot interferometer for CO2 detection - Pawar, Dnyandeo; Lo Presti, Daniela; Lemma, Enrico D.; Rainer, Alberto; Kumar, Ajay; Kanawade, Rajesh; Silvestri, Sergio; Schena, Emiliano; Massaroni, Carlo (IEEE Sensors Journal, 2024)
Monitoring carbon dioxide (CO2) gas is essential for numerous applications, but the detection of CO2 in miniaturized devices presents significant challenges. In this study, a polyethyleneimine/poly(ethylene glycol) (PEI/PEG) coated optical fiber Fabry-Perot interferometer (FPI) and its charge transfer process toward CO2 are investigated. Scanning electron microscopy and Fourier transform infrared spectroscopy were used to analyze the surface morphology and vibration bands of the PEI/PEG composite. The PEI/PEG composite Fabry-Perot (FP) cavity of length similar to 13 mu m is coated at the distal end of the single-mode fiber using a dip coating technique. A highly sensitive optical and low-cost FPI probe fabrication has displayed a linear sensitivity of 17.10 nm/% in the range of 0.31%-1.25% CO2 gas. The response and recovery times of the sensor are in a few tens of seconds. The enhanced performance of the sensor is primarily due to the protonation and charge transfer between CO2 gas molecules and PEI/PEG composite. Due to low-cost fabrication and high sensitivity, this FPI sensor can be used in a range of potential applications in bioprocessing, healthcare, and environmental monitoring.
Keywords: dip coating; Fresnel's reflection; Interference; monitoring; Optical fiber sensors; Optical fibers; polymer composite; Polymers; refractive index; sensitivity; Sensor phenomena and characterization; sensors; swelling; Temperature sensors

Investigating the visible range photoresponse of an organic single-crystal analogue of the green fluorescent protein - Virole, Vishal; Dabke, Niteen; Verma, Sahil; Kumar, Ajay; Pandya, Rinu; Husale, Sudhir; Vanka, Kumar; Gonnade, Rajesh; Kanawade, Rajesh (Nanoscale, 2025)
The growing demand for lightweight, flexible, semi-transparent and low-cost photodetectors (PDs) in wearable electronics and optical communication systems has prompted studies to investigate organic materials as feasible alternatives to conventional inorganic PDs. However, modern organic PDs often face responsivity, detectivity, and photoresponse speed limitations, particularly in the visible range. Here, we present the photoresponse of an organic single-crystal analogue of the green fluorescent protein (GFP) chromophore photodetector, fabricated on a silicon nitride substrate. A significant increase in photocurrent was detected upon illumination with visible wavelengths (532 nm, 630 nm, and halogen light). A remarkably consistent and repeatable photoresponse was obtained during the ON and OFF illumination cycles. The device showed the dependence of photocurrent on the applied bias voltages. The measured photocurrent, responsivity, detectivity, rise time, decay time, noise equivalent power and external quantum efficiency are studied for different wavelengths. Strikingly, the fabricated device demonstrates excellent performance in the visible region compared to several conventional organic and inorganic PDs. The observed responsivity and detectivity values for the device are 98 mA W-1 and 7.94 x 108 Jones, respectively. Furthermore, the device also exhibits rapid photoresponse dynamics with a rise time of 180 ms and a decay time of 152 ms. The excellent photodetection features indicate that the single crystal GFP could serve as a versatile broadband material for future applications in optoelectronics.

Isobavachalcone ameliorates Alzheimer disease pathology by autophagy-mediated clearance of amyloid beta and inhibition of NLRP3 inflammasome in primary astrocytes and 5x-FAD mice - Kour, Dilpreet; Khajuria, Parul; Sharma, Kuhu; Sharma, Alpa; Sharma, Ankita; Ali, Syed Mudassir; Wazir, Priya; Ramajayan, P.; Sawant, Sanghapal D.; Nandi, Utpal; Ahmed, Zabeer; Kumar, Ajay (Frontiers in Pharmacology, 2025)
Background and Aim Alzheimer's disease (AD) progresses with A beta plaque deposition and neuroinflammation. Given the complexity of AD pathology, single-target therapies have frequently failed in clinical trials. We hypothesized that a multitarget approach could yield better therapeutic outcomes. To this end, we identified isobavachalcone (IBC), a natural compound with dual pharmacological activity in reducing A beta plaques and neuroinflammation.Experimental Procedure Primary astrocytes were isolated from 3 to 4 days old C57BL/6J mice pups for in-vitro assays, while in-vivo studies were conducted on 5x-FAD mice. Protein alterations were evaluated using ELISA, western blotting, immunocytochemistry, and immunohistochemistry. Behavioral analyses included the radial arm maze, open field, and rotarod tests. Data from all in vitro and in vivo experiments were analyzed by using one-way ANOVA and post-hoc Bonferroni tests.Results In-vitro analyses in astrocytes demonstrated that IBC at 5 and 10 mu M concentrations induce AMPK phosphorylation through CAMKK2, promoting autophagy and inhibiting the NLRP3 inflammasome in primary astrocytes. IBC-treated astrocytes exhibited significant clearance of extracellular amyloid beta. Mechanistic studies highlighted autophagy as a key factor in reducing both NLRP3 inflammasome activity and A beta levels. Two months of treatment of 5x-FAD mice with IBC at 25 and 50 mg/kg significantly improved cognitive functions, as evidenced by enhanced memory and motor performance in behavioral tests. Subsequent brain tissue analysis revealed that IBC upregulated autophagic proteins to reduce the brain's amyloid beta levels, resulting in decreased expression of neuroinflammation markers.Conclusion IBC effectively ameliorates AD pathology through autophagy-mediated clearance of A beta and suppressing neuroinflammation in 5x-FAD mice.
Keywords: Alzheimer disease; Amyloid beta; Autophagy; isobavachalcone; neuroinflammation; NLRP3 inflammasome

Optimisation of metallic bismuth nanoparticle supported Pt-Bi(x%)/C hybrid electrocatalyst for cost effective and efficient hydrogen production in alkaline media - Dokhe, Revati; Ugale, Atul; Dube, Onkar; Varpe, Vaibhav; Galave, Chaitanya; Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Kumar, Ajay; Husale, Sudhir; Natu, Varun; Shevate, Rahul; et al. (International Journal of Hydrogen Energy, 2025)
The present study employed a simple mechanochemical method followed by 24-h ultrasonication to synthesize oxide-free metallic bismuth (Bi) nanoparticles. This was further used to synthesize a Pt-Bi(x%)/C (NC-x) hybrid electrocatalyst for the hydrogen evolution reaction in alkaline media. X-ray photoelectron spectroscopy and contact angle measurements reveal, Bi modifies the electronic structure and surface morphology of the Pt/C electrocatalyst, thus enhancing reaction kinetics and active site availability. The relative three-electrode study reveals that optimised NC-20 electrocatalyst reduces the overpotentials by 10.44 % and enhances the current density by 53 % compared to commercial Pt/C. The practical applicability of the NC-20 electrocatalyst was studied with the 13 cm2 single cell anion exchange membrane electrolyser. The catalyst demonstrates promising performance where the current density of NC-20//IrO2 relatively increases by 22.6 % compared to standard Pt/ C//IrO2, and shows continuous production and stable performance when monitored for 30 h.
Keywords: AEM; Bismuth nanoparticles; electrocatalyst; Full cell electrolysis; hydrogen evolution reaction; water electrolysis

Real-time estimation of blood oxygenation parameters from human foot sole during leg elevation: a preliminary study with diffuse reflectance spectroscopy - Kumar, Ajay; Lohchab, Viney; Pawar, Dnyandeo; Someshwar, Vimal; Mathe, Vikas; Husale, Sudhir; Kanawade, Rajesh (Optics and Laser Technology, 2025)
This study investigated the applicability of diffuse reflectance spectroscopy (DRS) for real-time and non-invasive measurement of blood oxygenation parameters (BOPs) such as reduced hemoglobin (RHb), oxyhemoglobin (HbO(2)), and oxygen saturation (SO2) from human foot sole during leg elevation. Seventeen (17) healthy male subjects aged between 21 to 39 years were included in this study. Diffuse reflectance spectra were recorded from measurement sites namely the 5th metatarsal, ball of great joint, calcaneum, and great toe of the human foot sole w.r.t. leg elevation angles such as 0(0), 15(0), 30(0), 45(0), and 60(0), respectively. The localized BOPs were derived from the recorded spectra. In addition, blood hemodynamic parameters (BHPs) such as heart rate (HR), SO2, perfusion index (PI), systolic blood pressure (SBP), and diastolic blood pressure (DBP) were also measured for each elevating angle. To study and assess the changes in BOPs and BHPs w.r.t. leg elevation, a One-way ANOVA test followed by a Tukey HSD post-hoc test was performed. We observed a statistically significant increase in RHb (p < 0.001) and a decrease in HbO(2) (p < 0.001) after 45 degrees of leg elevation, however, there was no statistically significant difference in SO2 (p = 0.74) and HR (p = 0.84) for each measurement site w.r.t. leg elevation, respectively. Furthermore, PI (p < 0.01), ankle SBP (p < 0.001) and DBP (p < 0.001) were decreased w.r.t. leg elevation. The obtained results are in agreement with the literature. The preliminary results suggest that DRS has the potential for real-time estimation of BOPs from the local sites of healthy human foot soles during leg elevation. Thus, it opens the possibility of DRS to monitor and evaluate the diagnosis and treatment of ischemia and edema during leg elevation of patients through BOPs measurement.
Keywords: diabetic foot ulcer; diffuse reflectance spectroscopy; Leg elevation; Oxygen saturation; Oxyhemoglobin; Reduced hemoglobin

Silicon incorporated tacrine: design, synthesis, and evaluation of biological and pharmacokinetic parameters - Kulkarni, Akshay S.; Ramana, Sreenivasa Rao; Nuthakki, Vijay K.; Bhatt, Shipra; Jamwal, Ashiya; Nandawadekar, Laxman D.; Jotshi, Anshika; Kumar, Ajay; Nandi, Utpal; Bharate, Sandip B.; Reddy, D. Srinivasa (RSC Medicinal Chemistry, 2025)
Tacrine, an orally bioavailable cholinesterase inhibitor, was previously used to treat Alzheimer's disease but was withdrawn due to hepatotoxicity. The unique structural features of tacrine have once again captured the interest of medicinal chemists. However, the blood-brain barrier (BBB) permeability hampered the development of the majority of its new analogs. Herein, we employed a silicon switch approach for improving the BBB permeability of CNS drugs with tacrine as a tool compound. The replacement of C2 methylene of tacrine with dimethyl silicon yielded `sila-tacrine' that inhibits acetylcholinesterase as well as butyrylcholinesterase with IC50 values of 3.18 and 6.09 mu M, respectively. Sila-tacrine competitively inhibits acetylcholinesterase while it is a non-competitive inhibitor of butyrylcholinesterase. The molecular docking results corroborated with the in vitro cholinesterase inhibition activity of tacrine vs. sila-tacrine. Sila-tacrine demonstrated metabolic stability in HLM and MLM and exhibited superior plasma exposure in an oral pharmacokinetic study in Swiss albino mice. However, tissue distribution studies revealed lower-than-expected brain levels due to efflux pump-mediated transport. This study offers a proof-of-concept for the silicon switch approach in improving the BBB permeability of CNS-active compounds.

Photoluminescence decay lifetime study of hydrothermally synthesized highly porous ruthenium-silica composite for optical dissolved oxygen sensing application - Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Pandya, Rinu; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Vanka, Kumar; Saha, Avishek; Kanawade, Rajesh (ACS Applied Nano Materials, 2026)
Pore size and surface area of photoluminescence (PL)-based transition metal composites play crucial roles in facilitating oxygen diffusion, thereby enhancing the response and sensitivity of optical dissolved oxygen (DO) sensors. In this study, we successfully applied the hydrothermal method to synthesize a porous ruthenium composite embedded in a silica matrix, demonstrating its effectiveness for optical DO sensing applications. The ruthenium-silica (Ru-Si) composites were synthesized using Ru(bpy)3 2+ and tetraethyl orthosilicate (TEOS) as precursors, with reaction temperatures ranging from 120 degrees C to 200 degrees C over a fixed duration of 4 h. The structural, morphological, and compositional characterization techniques confirmed the successful synthesis and evaluated the porosity, surface features, and chemical structure of the resulting composites. The optimized Ru-Si composite exhibited the highest porosity, characterized by a specific surface area of 996.78 m2 g- 1, and exhibited the highest decay lifetime of 8.14 mu s in deionized (DI) water, compared to other composites. Importantly, we demonstrate an excellent linear response of the synthesized Ru-Si composite to DO concentrations ranging from 2.58 to 11.16 mg L-1, with a Stern-Volmer constant of 0.12. Furthermore, a density functional theory study was conducted to investigate the electronic transitions and to elucidate the oxygen quenching mechanism of the excited Ru composite with molecular oxygen. The calculated photophysical parameters of the composite show good agreement with the experimental results. Preliminary results suggest that the synthesized Ru-Si with high pore size and surface area could be an efficient and effective composite for use in DO sensing applications.
Keywords: Hydrothermal method; opticalDO sensor; oxygen quenching; photoluminescent; ruthenium composite

Polysulfone-based polymer carbon dot membrane for optical dissolved oxygen sensing application - Kadam, Rutuja; Hattale, Gangadhar; Virole, Vishal; Pal, Sanjivani; Abraham, Athira; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Banpurkar, Arun; Kanawade, Rajesh; Saha, Avishek (Chemistry-An Asian Journal, 2026)
The precise monitoring of dissolved oxygen (DO) is essential across industrial, environmental, and biomedical applications. However, the state-of-the-art DO sensing methods often suffer from inherent limitations, which hinder their effectiveness for real-time and long-term DO monitoring. Optical DO sensing, despite its advantages, utilizes expensive metal complexes and is prone to photobleaching and slow response time. Here, we introduce a novel polymer carbon dot (PCD) as a promising candidate for lifetime-based optical DO sensing. The PCD is a metal-free, nontoxic, fluorescent, long decay-lifetime material that is synthesized through hydrothermal method. Our fluorescent PCD exhibits high emission quantum yield (24.32%), long decay-lifetime (10.43 & micro;s), and a linear response to DO concentrations ranging from 0.7 to 12.7 mg/L, with a Stern-Volmer constant of 0.1115. Further, to obtain better oxygen diffusion, high porosity, optical transparency, and high flexibility, PCD was embedded into a polysulfone matrix (PSF_PCD). The PSF_PCD membrane shows better results for the decay lifetime (9.4 & micro;s), surface energy (40.26 mN/m), and average pore diameter of 5 nm. Hence, the obtained results demonstrate the applicability of the PCD in optical DO sensors for real-time and long-term monitoring of DO levels.
Keywords: decay lifetime; dissolved oxygen; Hydrothermal method; polymer carbon dots; polysulfone-based membrane